THE ROLE OF BUDGETARY PARTICIPATION, CLARITY OF BUDGET OBJECTIVES IN IMPROVING MANAGERIAL PERFORMANCE WITH LEADERSHIP STYLE AS MODERATION: AN EMPIRICAL STUDY IN UNIVERSITY X - Rikawati, Rikawati; Korawijayanti, Lardin; Arbainah, Siti; Nikmatuniayah, Nikmatuniayah; Rois, Muhammad (KEUNIS, 2024)
This research aims to evaluate the relationship between budgetary participation, clarity of budget objectives, and leadership style on managerial performance at the University X. The approach used is quantitative descriptive, with the collection of primary data through the distribution of online questionnaires to 47 respondents selected using purposive sampling.The data analysis tool used is Moderated Regression Analysis. The research findings indicate that budgetary participation and clarity of budget objectives have a positive impact on managerial performance. However, leadership style only reinforces the relationship between budgetary participation and managerial performance, while not significantly influencing the relationship between the clarity of budget objectives and managerial performance.These findings provide important insights that budgetary participation and clarity of budget objectives can be determinants of managerial performance, with leadership style playing a reinforcing role in this relationship. The implications of this research can be used as a basis for management to enhance performance by improving budgetary participation and clarity of budget objectives, taking into account the role of leadership style in this context